Simulation Of Series And Parallel Hydraulic Hybrid Myvi - Leong, Yong Sheng (Universiti Sains Malaysia, 2021)
The paper compares the fuel economy of Perodua Myvi with 2 different architectures of hydraulic hybrid vehicle which are parallel and series architectures. The simulation was done to predetermine the feasibility of transforming conventional Myvi to a hydraulic hybrid Myvi. The fuel economy was simulated with backward-facing model on the Malaysian drive cycle using MATLAB coding. A rule-based control strategy was manipulated manually to fulfill the requirement with respect to the drive cycle. The parallel architecture shows a good improvement on fuel economy which is 97% while 47% in series architecture. However, even the parallel hybrid would take 12.4 years for the return of investment costing which is infeasible.